Government Efforts in Promoting Community Participation in the Development of Village Roads - Siti Sofiaton (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2023)
This research departs from the problem of the decreasing level of community participation in cooperation such as to maintain what already exists; in other respects, it can be said that drainage or ditches are not cared for so that water freely finds its way, causing damage to the main road and unstable soil conditions and broken roads. This study aims to determine the government's efforts to re-grow the participation of the Kaliguwo village community and the results of village road infrastructure development in Kaliguwo village, Kaliwiro sub-district, Wonosobo. The framework used in this study is development sociology and participation theory. This theory prioritizes economic and sociological aspects. Development is a process of planned and desired change. The opinion stated that development in terms of the process of change, where the change is carried out by the community itself because the desire for change itself is a community, because it is based on the existence of community needs from various aspects of everyday human life. Here, the government provides examples or describes ideas so that the community can work together with village officials to carry out activities in the form of togetherness and submit deliberations on how to do so that the community can carry out activities as usual in cooperation or activities related to this development. Even though not all people participate, road infrastructure development must continue. Because with the construction of road infrastructure, the community's economy is increasing and vehicles are getting easier in and out of the village.